PENGARUH PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TERHADAP KEMAMPUAN BERMAIN GAMELAN DEGUNG SISWA SMPN 2 LEMBANG - Fadhilatunisa Salsabila, - (2019)
Reseacrhh is called "The Influence Of The Active Learning On Ability To Play Gamelan Degung Student SMPN 2 Lembang. Aims to improve students ability play gamelan degung. This research in a true experiment but design randomized control group pretest-posttest approach in quantitative. Findings the results of the research this proves changes in the capacity play gamelan degung to rise. By applying active learning to the process teaching becomes more active. Versed immediately make color, make students easy recollect and not rapid forget. Experimentation in accordance with the procedures that is be implemented in stages through step learning systematic. As for the effects of the implications active learning in learning gamelan degung class VIII SMPN 2 Lembang can give a positive impact them into learning gamelan degung in improving the ability to play effectively and efficiently.